The Impact of Fintech on Financial Inclusion and Regional Economic Growth - Mansyur, Khusnul Khotimah (Journal of Economic Growth and Development Review, 2025)
This study analyzes the impact of financial technology (fintech) on financial inclusion and regional economic growth in Indonesia during the period 2018-2024 using a mixed methodology approach. The results show that fintech penetration in Indonesia has experienced significant growth especially since the COVID-19 pandemic, although with uneven geographical distribution. Quantitative analysis reveals a positive relationship between fintech adoption, financial inclusion indicators, and regional economic growth, with around 54% of the total effect of fintech penetration on GRDP per capita mediated by increased financial inclusion. This study identifies five main mechanisms that explain the impact of fintech: reduced transaction costs, expanded access to credit, formalization of the informal economy, accelerated entrepreneurship, and increased geographic inclusiveness. It also finds that the impact of fintech is greater in rural and remote areas than in urban areas, highlighting its potential to reduce the gap in access to finance between regions. Internet infrastructure, digital literacy, and regulatory quality play important moderating roles in strengthening the positive impact of fintech. The existence of spatial spillover effects suggests that the economic benefits of fintech can spread to surrounding areas. This study recommends a series of policies to maximize the potential of fintech as a catalyst for inclusive regional economic development in Indonesia.